Relevansi Promosi terhadap Minat Nasabah Dalam Melakukan Transaksi Di Bank Syariah Mandiri KC Kepanjen - Anita Rahmayanti (Department of Islamic Economic Law, Institut Agama Islam (IAI) Al-Qolam, 2018)
This research is aims to know how the promotion affected of customer interest in transactions at Sharia Mandiri Bank Kepanjen. This research was conducted by means of quantitative descriptive. Methodology of data collection were carried out by using questionnaires and distributed to the customers of Sharia Mandiri Bank Kepanjen. The research samples taken 100 respondents who are conducted the transaction at Sharia Mandiri Bank Kepanjen, the researcher used Sampling Incidental technique. Data analysis in this research include validity test, reliability test, multiple regression test, statistic test through t-test, f-test, and coefficient of determination (R2), and classical assumption test. The data analysis conducted by SPSS 22 version. Based on the research result there are influence of advertising variable, personal sales, sales promotion, publicity, and direct marketing of customer interest in transaction at Sharia Mandiri Bank Kepanjen. Based on the results of multiple linear regression analysis obtained R2 is 57.7% while the remaining 42.3% is explained by other variations outside the variable model examined in this research. Promotion Variables that have the most influence on the customers interest in transactions at Sharia Mandiri Bank Kepanjen is a personal sales promotion. From the data analysis obtained F 25,709 with a significance value of 0.000, because the significant probability is smaller than 0.05 it means Ho rejected and Ha accepted. This results shown that the promotion can affect the customers’ interest.